NaOH impregnated sepiolite based heterogeneous catalyst and its utilization for the production of biodiesel from canola oil. Issue 3 (1st February 2019) - Aslan, Sema; Aka, Necdet; Karaoglu, M. Hamdi
ABSTRACT: NaOH/sepiolite nanocomposite heterogenous base catalyst (NaOH/sep.) was prepared via impregnation process and tested in a three-neck flask equipped with thermometer and reflux condenser for the production of biodiesel from transesterification of canola oil in an excess amount of methanol. The ratio of NaOH and sepiolite was selected as 1:4. The influence of various operational parameters was examined such as methanol to oil molar ratio, catalyst dosage, and reaction temperature. Untreated sepiolite and NaOH loaded sepiolite were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, Scanning electron microscopy and Energy dispersive spectroscopy analysis. Overall NaOH/sep. based biodiesel production yield was examined by the help of Gas chromatography-mass spectrometry analysis. The yield was calculated from the peak areas as 80.93% which is better than that of expensive catalysis system using studies.